The Evolution of the BRICS Trade Alliance: Analysing Strategic Partnerships and Economic Interdependence in the Global South - Haryono, Haryono (Eastasouth Institute, 2024)
The BRICS alliance—comprising Brazil, Russia, India, China, and South Africa—has emerged as a vital platform for fostering economic interdependence and strategic partnerships in the Global South. This study employs a normative juridical approach to analyze the legal frameworks, trade mechanisms, and institutional structures underpinning the alliance. Findings reveal that initiatives such as the New Development Bank, intra-BRICS trade agreements, and currency swap arrangements have strengthened collaboration among member states. However, challenges such as trade imbalances, geopolitical tensions, and institutional inefficiencies persist. This paper highlights the potential of BRICS to reshape global economic governance by advocating for equitable trade practices and promoting sustainable development in the Global South.